Dakwah Kultural dalam Upacara Adat Ngalaksa - Mukhlis Aliyudin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2016)
Religion and culture continue to color the human life. In fact, the two are inseparable, complementary to each other and give meaning. Religion is always alive and embedded in cultural values, otherwise the culture is always cooperative with religious values. Not a bit of cultural values to accommodate religious values. And in between the spread of religious and cultural value to the community is by propaganda. As happened in the community Rancakalong Sumedang ceremony Indigenous Ngalaksa, which indirectly has happened blend of religious values with the local cultural values, and propaganda with the culture in this area is considered appropriate because it has made this region a peaceful, secure, peaceful, and mutual respect among fellow citizens.